Cron Job Implementation for Automated Data Processing and Transfer in Cloud Infrastructure - Wibowo, Apriansyah; Fathimah, Aisya; Waskito, Deswal; Aprilianto, Rizky Ajie (Universitas Negeri Semarang, 2025)
The rapid growth of cloud computing has necessitated efficient and automated solutions for data management in cloud infrastructure. Manual data processing and transfer methods are prone to delays, errors, and inefficiencies, particularly in real-time applications. This study proposes a systematic approach to automate data processing and transfer using cron job, PHP script logic, and Cloud Panel integration. A MySQL database was designed with two tables: data_now for real-time data and data_one_hour for scheduled transfers at one-hour intervals. Php script were developed to automate data transfer logic, while cron job were configured on the Cloud Panel to execute these scripts at predefined intervals. The system was tested in a cloud environment, demonstrating error-free, hourly data transfers with significant improvements in efficiency, accuracy, and timeliness. Results showed that the automated system reduced manual workload, ensured real-time data consistency, and optimized resource utilization. This study provides a scalable and reliable framework for automating data workflows in cloud-based systems, offering practical solutions for industries such as healthcare, finance, and IoT. The findings contribute to the field of cloud automation by presenting a robust approach that can be readily implemented across various organizational infrastructures.